2017
DOI: 10.1016/j.celrep.2017.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Docking Is a Key Target of Local PI(4,5)P2 Metabolism in the Secretory Pathway of INS-1 Cells

Abstract: SUMMARY Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) signaling is transient and spatially confined in live cells. How this pattern of signaling regulates transmitter release and hormone secretion has not been addressed. We devised an optogenetic approach to control PI(4,5)P2 levels in time and space in insulin-secreting cells. Combining this approach with total internal reflection fluorescence microscopy, we examined individual vesicle-trafficking steps. Unlike long-term PI(4,5)P2 perturbations, rapid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…This discrepancy to our live cell work indicates that intact cellular membranes are different with regards to PtdIns aggregation, either because of unknown cellular mechanisms that prevent clustering of PtdIns, or because disruption of cellular membranes promotes PtdIns aggregation. We demonstrate here that permeabilization of the cells with α‐toxin causes slow clustering of PtdIns in the plasma membrane, reminiscent of previous reports . It can be envisioned that such treatment relieves physiological membrane tension, and that this in turn leads to membrane ruffling and clustering of PtdIns, syntaxin‐1 and other proteins.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This discrepancy to our live cell work indicates that intact cellular membranes are different with regards to PtdIns aggregation, either because of unknown cellular mechanisms that prevent clustering of PtdIns, or because disruption of cellular membranes promotes PtdIns aggregation. We demonstrate here that permeabilization of the cells with α‐toxin causes slow clustering of PtdIns in the plasma membrane, reminiscent of previous reports . It can be envisioned that such treatment relieves physiological membrane tension, and that this in turn leads to membrane ruffling and clustering of PtdIns, syntaxin‐1 and other proteins.…”
Section: Discussionsupporting
confidence: 83%
“…We show here that acute depletion of PtdIns(4,5)P 2 in the plasma membrane strongly inhibits exocytosis, which confirms earlier reports . However, PtdIns(4,5)P 2 depletion did not cause changes in granule docking, and the density of docked granules was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of PIPKIg90 activity with UNC3230 also inhibited fibronectin secretion. These data suggest that PIPKIg90 activity is essential for fibronectin secretion, which is consistent with the role of PIP 2 in vesicle docking (7,8,54).…”
Section: Discussionsupporting
confidence: 83%
“…Phosphatidylinositol 4 phosphate 5-kinase type I g (PIPKIg90) catalyzes ATP-dependent phosphorylation of phosphatidylinositol 4-phosphate to generate phosphatidylinositol 4,5-bisphosphate (PIP 2 ), which functions as a vesicle docking site, thus regulating vesicle exocytosis (7,8). It is also a precursor of several lipid second messengers, such as phosphatidylinositol 3,4,5-triphosphate, inositol 1,4,5-triphosphate, and diacylglycerol.…”
mentioning
confidence: 99%
“…In contrast, rapid PIP 2 reduction in the plasma membrane of INS1 cells strongly inhibited secretion but not sytaxin1a clustering. However, selective local PIP 2 reduction at vesicle docking sites caused vesicle undocking from the plasma membrane at these sites [166]. Another very recent study in live INS1 cells revealed also no evidence for PI(3,4,5)P3 or PIP 2 association with syntaxin clusters and actually no evidence for PIP 2 clustering at all [167].…”
Section: Pip 2 Supports Fusion But Its Role In Tsnare Clusters Is Quementioning
confidence: 96%